2020
DOI: 10.1111/jfbc.13169
|View full text |Cite
|
Sign up to set email alerts
|

Novel insights into the fruit and seed extracts ofMorinda morindoides(Baker) Milne‐Redh: HPLC‐ESI‐Q‐TOF‐MS profiling, antioxidant, and enzyme inhibitory propensities

Abstract: In this study, we attempted for the first time to determine the phytochemical compositions and biopharmaceutical properties of the methanolic and aqueous extracts of Morinda morindoides fruits and seeds. Antioxidant propensities of the extracts were determined via free radical‐scavenging, phosphomolybdenum, metal chelating, and reducing power assays. Inhibitory activities against cholinesterases (acetylcholinesterase (AChE) and butyrylcholinesterase (BChE)), tyrosinase, α‐amylase, and α‐glucosidase were assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 42 publications
1
1
0
Order By: Relevance
“…, whereby the highest anti-tyrosinase effect was found in the root methanol extract with IC 50 of 3.55 ± 0.35 mg/ml compared to other tested extracts of C. cajan. Besides, in one of our previous work, the methanolic extracts of M. morindoides was noted to have remarkable inhibitory propensities the enzymes tested in the current study, including tyrosinase(Sinan et al, 2020). Kim Lien et al (2019) also reported iso-…”
supporting
confidence: 66%
See 1 more Smart Citation
“…, whereby the highest anti-tyrosinase effect was found in the root methanol extract with IC 50 of 3.55 ± 0.35 mg/ml compared to other tested extracts of C. cajan. Besides, in one of our previous work, the methanolic extracts of M. morindoides was noted to have remarkable inhibitory propensities the enzymes tested in the current study, including tyrosinase(Sinan et al, 2020). Kim Lien et al (2019) also reported iso-…”
supporting
confidence: 66%
“…Besides, in one of our previous work, the methanolic extracts of M . morindoides was noted to have remarkable inhibitory propensities the enzymes tested in the current study, including tyrosinase (Sinan et al., 2020). Kim Lien et al.…”
Section: Resultsmentioning
confidence: 62%